When Does Regulation Distort Costs? Lessons from Fuel Procurement in US Electricity Generation: Comment - Han, Jin Soo; Houde, Jean-François; van Benthem, Arthur A.; Abito, Jose Miguel (American Economic Review, 2021)
We revisit one of the results in Cicala (2015) and show that the previously estimated large and significant effects of US electricity restructuring on fuel procurement are not robust to the presence of outliers. Using methodologies from the robust statistics literature, we estimate the effect to be less than one-half of the previous estimate and not statistically different from zero. The robust methodology also identifies as outliers the plants owned by a single company whose coal contracts were renegotiated before discussions about restructuring even started. (JEL D83, O13, O33, Q16)